Space4Energy: come gli asset spaziali possono aiutarci a risolvere il problema dell’energia (GEOmedia, 2023)
At the end of 2019, the European Commission presented the "European Green Deal", setting the goal of makingEurope climate neutral by 2050.This goal implicitly defined the need to rapidly change our energy supply systems, which currently represent the 75% of EU greenhouse gas emissions. Recent international events in Eastern Europe have shown clearly and dramatically the urgency of an energy infrastructure that makes Europe not only climate-neutral, but also as independent and autonomous as possible.Finding an effective way to deal with the current scarcity of energy resources and at the same time the problem of climate change requires a complete transformation of the existing energy systems and the best possible exploitation of the so-called renewable energy sources.